马来西亚华语的语序使用 ：以新山和吉隆坡的两代华人为例 = Word order in Malaysia Mandarin Chinese : a study based on two generations of Malaysian Chinese in Johor Bahru and Kuala Lumpur - 张慧莹 Teo, Hui Ying (2019)
汉语是世界上使用人数最多的语言。汉语变体遍布于各个华人地区，马来西亚就是其中之一。由于马来西亚的历史背景、教育政策、语言环境都和中国大陆不同，使得马来西亚华语和中国大陆普通话之间在语音、词汇及语法上都存在差异。马来西亚是一个多元种族和多语言的国家。语言接触和语言变异无时无刻都在发生。独特的语言环境使得马来西亚华语研究逐渐受到学者们的重视。本文采用问卷调查的形式，以马来西亚年长一代和年轻一代的华人为研究对象，考察了马来西亚华人社会在进行口语交际时对马来西亚华语语序或是中国大陆普通话语序的使用频率。本文也参考了新加坡华语特殊语序现象，为问卷调查的口语语料扩大范围，并同时考察马来西亚华语语法系统中是否也存在与新加坡华语语序相同的结构。研究结果显示无论是以年龄层、地区、性别或方言掌握程度为考量，马来西亚华人社会在进行口语交际时偏向更常或只使用中国大陆普通话语序。不同年龄层的语言能力、用语习惯及语言态度都是影响语序发生变异的其中原因。另外，马来西亚华语语法系统中存在与新加坡华语特殊语序现象相同的结构。随着普通话全球化的影响，马来西亚华人社会在马来西亚华语语序的使用上向着中国大陆普通话语序趋同的现象越发明显。Being one of the varieties of Mandarin Chinese, Malaysia Mandarin Chinese differs from Mainland Mandarin Chinese (i.e. Putonghua) in pronunciation, vocabulary and grammar due to Malaysia's historical background, education policy and language environment. Previous studies found that some word orders in Malaysia Mandarin Chinese are unique and thus different from that of Putonghua due to its contact to local Chinese dialects (e.g., Hokkien and Cantonese) and other languages (e.g., English and Malay). This study aims to investigate the word order used by different generations of Malaysian Chinese, particularly, whether the speakers tend to choose the word orders unique to Malaysia Mandarin Chinese or the word orders typically found in Putonghua. To extend the scope of the spoken corpus for the questionnaire, this study also refers to some unique word orders found in Singapore Mandarin Chinese and examines whether those orders are used in Malaysia Mandarin Chinese.The results of this study show that regardless of generation, region, gender and dialect proficiency, Malaysian Chinese tend to use Mainland Mandarin Chinese word order more often in oral communication. Language capabilities, language preference and language attitudes of different generations are the reasons that influence the variation of word order. In addition, the Malaysia Mandarin Chinese grammar system shows a structure similar to that of Singapore Mandarin Chinese in terms of word order. With the influence of the globalization of Putonghua, the phenomenon that the Malaysia Mandarin Chinese word order is converging towards the Mainland Mandarin Chinese is becoming more and more apparent.